Penerapan Pembelajaran Kooperatif Tipe NHT Ditinjau dari Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Dasar - Nurul Saila; Faridahtul Jannah; Dzaky Isyuniandri (Departement of Mathematics Education, 2023)
The background of this research is the importance of students' mathematical problem-solving abilities in learning mathematics. This study aims to determine how to increase elementary school students' mathematical problem solving abilities through the application of NHT type cooperative learning and to increase elementary school students' mathematical problem solving abilities through conventional (expository) learning. This research is a quasi-experimental research with Pretest-Postest Control Group design. The research instrument is a test of mathematical problem solving ability. This research was conducted at a public elementary school with A accreditation. The population of this study was students of SDN Kanigaran 3 Probolinggo, East Java, with two classes of fifth grade students as respondents. VA class students as the experimental class and VB class students as the control class. The data in this study were analyzed using descriptive statistics and inferential statistics. The results of this study indicate: (a) the average mathematical ability of elementary school students through NHT type cooperative learning is better than that of elementary school students through conventional (expository) learning, and (b) the improvement of elementary school students' mathematical abilities through cooperative learning type NHT is better than elementary school students through conventional learning (expository)